Organizational Support as a Catalyst for Professionalism and Stress Management in Complex Religious Service Systems: A Systematic Literature Review of the Hajj Context - Hemmy Fauzan; Ade Sofyan Mulazid; Suhendra Suhendra; Desmadi Saharuddin; Bahrul Yaman; Alaa Mustafa Abdelmaksud Abouagila (Yayasan Keluarga Guru Mandiri, 2026)
In an era characterized by digital transformation and heightened expectations for service excellence, understanding how organizational support, professionalism, and stress management interact has become increasingly vital. This study aims to synthesize and contextualize existing evidence on these relationships within large-scale, culturally embedded service environments—particularly the Hajj system—through a Systematic Literature Review (SLR). Using the PRISMA 2020 protocol and the TCCM framework, 41 peer-reviewed articles published between 2015 and 2025 were systematically analyzed. The review employed the Job Demands–Resources (JD-R) and Conservation of Resources (COR) models as theoretical anchors while incorporating cross-sectoral and cross-cultural perspectives. Findings reveal that organizational support functions not merely as a buffer against stress but as a transformative mechanism that fosters ethical commitment, mindfulness, and adaptive professionalism. Interestingly, ethical leadership and spirituality emerged as critical mediators linking support mechanisms to service performance—an aspect often overlooked in Western-centric frameworks. Moreover, digital transformation was found to operate as a paradoxical driver, enhancing efficiency yet potentially triggering technostress unless balanced with empathy and inclusive leadership. The review extends the JD-R model by integrating cultural and spiritual dimensions, reframing professionalism as a moral and relational construct. The study contributes a novel conceptual synthesis that bridges ethical, technological, and psychological dimensions of organizational behavior. Practically, it urges institutions—especially in religious or collectivist service systems—to design integrative strategies that harmonize operational performance with human well-being. Future research should adopt longitudinal and mixed-method approaches, exploring AI-enabled mindfulness interventions and cross-cultural comparisons to refine context-sensitive models of organizational resilience. This study contributes by extending the Job Demands–Resources model through the integration of cultural and spiritual dimensions, offering a novel conceptual synthesis that bridges ethical, technological, and psychological aspects of organizational behavior. It also provides practical insights for designing integrative strategies that align digital efficiency with human well-being, particularly in culturally embedded service systems.